The Audit Value Factor - Samson, Danny (Milton : Auerbach Publishers, Incorporated, 2018)
The Audit Value Factor: Making Management's Head Turn empowers readers with a systematic method to build and maintain a value-centric internal audit organization. The book explores how to identify, quantify, and articulate value for customers. It details six critical success factors: Value propositions that link directly to customer needs Fostering customer relationships using the CREATE model Talent development using the TEAM model Risk expertise that raises awareness, understanding, and action Change management and process optimization using the SMART model Data analytics that provide powerful insights to operations The Audit Value Factor offers easy to use tools and practical strategies that deliver tangible and immediate benefits for the internal audit team. Praise for The Audit Value Factor: Making Management's Head Turn "Daniel Samson, the inspiring and forward-thinking CAE at SRI International, has created an essential guide to adding value through Internal Audit in his new book The Audit Value Factor. It's an important addition to any internal auditor's toolkit, with helpful suggestions on topics ranging from talent planning to data analytics. I highly recommend it to any internal audit professional looking to "up their game." Laurie A. Hanover, CIA, CAE Sunrun Inc. "Internal Auditors often strive for a seat at the table, ' be it with Business Leaders, Senior Management, the Board, or really, any significant decision maker in an organization. In The Audit Value Factor, Dan Samson provides the roadmap to ensuring that Internal Audit gets not only that seat at the table, but also that role of a critical business partner that is valued in facilitating change and helping an organization achieve its goals." Brian Tremblay, CAE Acacia Communications "Great audit functions generate value and build leadership capacity from staff to CAE. The Audit Value Factor's compelling examples, data, and actionable tools enable auditors at every level to build relationships of trust, ask the right questions, and deliver powerful insights to their organization." Dr. Kathryn Bingham, Executive Coach and CEO, LEADistics LLC
OCLC-licensed vendor bibliographic record.
Keywords: Auditing, Internal; BUSINESS & ECONOMICS -- Accounting -- General; BUSINESS & ECONOMICS -- Auditing; BUSINESS & ECONOMICS -- Management Science